Discrete-Time Adaptive Control Algorithm for Coordination of Multiagent Systems in the Presence of Coupled Dynamics - Aly, Islam A.; Dogan, K. Merve (Proceedings of the ... IEEE/RSJ International Conference on Intelligent Robots and Systems, 2023)
Discrete-time architectures have an advantage over their continuous counterparts as they can be directly executed on embedded hardware without the need for dis-cretization, and discretization can result in a loss of stability margin. This paper presents a discrete-time adaptive control architecture for uncertain scalar multi agent systems with coupled dynamics. Our strategy includes observer dynamics to handle the unmeasurable coupled dynamics and a user-assigned Laplacian matrix for coordination of the multiagent system. An illustrative example is presented to show the efficacy of the proposed control architectures.